Teknik Penyemprotan Pestisida pada Pertanaman Mentimun : Pengaruhnya Terhadap Tingkat Penutupan dan Sebaran Droplet - Moekasan, Tonny Koestoni (Jurnal Hortikultura Indonesia, 2019)
Spraying technique of pesticides that are commonly carried out by cucumber farmers in Indonesia is very diverse, so it is needed to be evaluated to find out the right way to spray. This experiment aimed to determine the effect of nozzle swing on the level of coverage and distribution of droplets. In addition, it is also to find out the effectiveness of pesticides used in pests and diseases control in cucumber cultivation. The experiment was carried out at Margahayu Experimental Garden (± 1 250 m asl.), Indonesian Vegetable Research Institute in Lembang, West Java, from July to October 2015. The experiment was arranged using paired comparisons and each treatment was repeated four times. The treatment tested is how to swing the nozzle with the position: (A) above the plant canopy facing down and moving forward and (B) below and swinging towards the plant at an angle of 45o. Results showed that the second nozzle swinging method (B) gave a higher level of coverage and distribution of droplets than that produced by the first nozzle swinging method, so the pesticide efficacy in treatment B was also higher. Keywords: efficacy, financial analysis, pesticide, spray volume